Stylistic features of Uzbek media texts - Xudoyberdiyeva Shirinoy (Лучшие интеллектуальные исследования, 2024)
Annotation: Today, mass information delivery, influencing people, and sharing news through the media are becoming widespread. In Uzbek content also, the electronic press has different stylistic features, this article presents the main purpose of the media language, its lexical-stylistic features in the Uzbek press and their examples.